Phytobezoar - S. R. Sundoro; W. T. Karjomanggolo; L. A. Tamaela (Indonesian Pediatric Society, 1974)
The present report is a case of phytobezoar, of which banana was the cause of the formation of the mass and which was removed by way of gastrostomy.